2009
DOI: 10.1007/s12550-009-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Trichothecene-induced cytotoxicity on human cell lines

Abstract: Trichothecene cytotoxicity of type A (T-2 toxin and HT-2 toxin), type B (deoxynivalenol, DON, and nivalenol, NIV), and type D (satratoxins G and H) compounds was determined comparatively by using eight permanent human cell lines (Hep-G2, A549, CaCo-2, HEp-2, A204, U937, RPMI 8226, and Jurkat). Viability of cells was measured by a water-soluble tetrazolium (WST-1) reagent cell proliferation assay assessing mitochondrial metabolic activity. Toxicity was expressed as the toxin concentration inhibiting 50% of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 40 publications
4
35
0
Order By: Relevance
“…Immunotoxicity of both mycotoxins demonstrated in this study was in agreement with data obtained by Nielsen et al (2009) by assaying the same B human lymphoid cell line. On other human lymphoid cell lines different IC 50 values were calculated, and values obtained for HT-2 were 10 times lower than those calculated for T-2 (Visconti et al, 1991).…”
Section: Discussionsupporting
confidence: 90%
“…Immunotoxicity of both mycotoxins demonstrated in this study was in agreement with data obtained by Nielsen et al (2009) by assaying the same B human lymphoid cell line. On other human lymphoid cell lines different IC 50 values were calculated, and values obtained for HT-2 were 10 times lower than those calculated for T-2 (Visconti et al, 1991).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, influence on several basic metabolic parameters in human primary hepatocytes was shown (Königs et al 2008). In addition, a comprehensive study indicated comparable high levels of DON toxicity between nine different human cell lines (Nielsen et al 2009b). These data suggest that the current research focus on lymphoid cell lines may lead to an underestimate of the toxic potential of DON.…”
Section: Introductionmentioning
confidence: 79%
“…Nielsen et al 2009b), respond differently compared to the more resistant Hep-G2 and A204 cells. Distinct increases in FOS levels, induced by treatment of cells with 1 µmol/l DON for 3 h, were observed in Hep-G2 and U937 cells…”
mentioning
confidence: 93%
“…can be found in a comprehensive review published earlier [74]. It is also important to note that application of multiple cell lines of different origins to test same mycotoxins reveals more accurate estimations of toxicity particularly for toxins with moderate to low cytotoxic potency [74,75]. Recently a study reported the generation of reactive oxygen species (ROS) and mammalian heat shock protein (Hsp) 70 expression in green monkey kidney (Vero) cells upon concurrent exposures to Fusarium mycotoxins, ZEN and T-2 toxin as a detection strategy to evaluate toxicity of these mycotoxins [23].…”
Section: Cbbs For Biotoxin Detection: Examples From Major Applicatmentioning
confidence: 99%